2021
DOI: 10.1079/hai.2021.0023
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the Social, Behavioral, and Academic Effects of Classroom Pets on Third and Fourth-Grade Students

Abstract: Limited research has documented the benefits of animals for children’s learning and development, with a growing number of elementary school teachers incorporating pets into their classrooms. This study assessed the social, behavioral, and academic effects of the presence of small, resident classroom animals for third and fourth-grade students across the United States. A total of 591 students from 41 classrooms (pet cohort = 20; no pet cohort = 21) and 19 schools participated. Classroom animals included guinea … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…The materials developed can be applied to a variety of settings and populations and may be particularly contributive to research with populations experiencing complex diagnoses that would limit valid self-report approaches to measurement (McCullough et al, 2019). The revised FACES coding manual and supplemental guidelines allow for clarity of code application to audiovisual data of real-world settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The materials developed can be applied to a variety of settings and populations and may be particularly contributive to research with populations experiencing complex diagnoses that would limit valid self-report approaches to measurement (McCullough et al, 2019). The revised FACES coding manual and supplemental guidelines allow for clarity of code application to audiovisual data of real-world settings.…”
Section: Discussionmentioning
confidence: 99%
“…A need remains for robust quantitative tools that can be used in real-world settings to measure momentary changes in emotion regulation in adolescents. This is particularly true for populations with complex diagnoses and psychosocial or learning impairments that would preclude participants from being able to provide valid self-report information (McCullough et al, 2019). Even in neurotypical populations, use of self-report instruments to assess emotional expressivity can be problematic.…”
Section: Introductionmentioning
confidence: 99%
“…However, prior research has demonstrated that interactions with animals have been associated with positive outcomes related to empathy and prosocial behavior (Daly & Morton, 2006; Mueller, 2014; Poresky & Hendrix, 1990). Prior research has also found that the presence of an animal (such as in a classroom setting) resulted in significant changes in socially oriented behavior, such as a reduction of aggressive behavior and parent‐ and teacher‐reported increases in prosocial behavior (Kotrschal & Ortbauer, 2003; McCullough et al, 2021).…”
Section: Introductionmentioning
confidence: 99%